Definition and predictors of early recurrence in neoadjuvantly treated esophageal and gastroesophageal adenocarcinoma: a dual-center retrospective cohort study - Rompen, Ingmar F.; Billeter, Adrian; Crnovrsanin, Nerma; Peters, Leila; Neuschütz, Kerstin J.; Musa, Julian; Bolli, Martin; Fourie, Lana; Kraljevic, Marko; Saeedi, Mohammed al; Nienhüser, Henrik; Müller, Beat P. (Annals of surgical oncology, 2025)
Early recurrence after esophagectomy is often used as a surrogate for aggressive tumor biology and treatment failure. However, there is no standardized definition of early recurrence, and predictors for early recurrence are unknown. Therefore, we aimed to define an evidence-based cutoff to discriminate early and late recurrence and assess the influence of neoadjuvant treatment modalities for patients with esophageal or gastroesophageal-junction adenocarcinoma (EAC).